Evaluation of needle biopsy as a potential risk factor for local recurrence of Wilms tumour in the SIOP WT 2001 trial. (July 2019) - Irtan, Sabine; Van Tinteren, Harm; Graf, Norbert; van den Heuvel-Eibrink, Marry M.; Heij, Hugo; Bergeron, Christophe; de Camargo, Beatriz; Acha, Tomas; Spreafico, Filippo; Vujanic, Gordan; Powis, Mark; Okoye, Bruce; et al.
Abstract: Rationale: The impact of biopsying Wilms tumour (WT) at diagnosis on assigning the tumour stage and recommended treatment remains controversial. To address this important question, we analysed the potential association of all types of biopsy with local recurrence in patients treated in the SIOP WT 2001 trial, where needle biopsy was permitted without 'upstaging' the tumour to stage III. Only open biopsy required treatment as stage III. Methods: Among 2971 patients with unilateral WT (stages I-IV), 420 relapsed (139 local). Risk factors for recurrence were analysed by Cox proportional hazard methods. Results: Biopsy was performed in 969 of 2971 (33%) patients (64% cutting needle, 30% fine needle aspiration [FNA] and 6% open biopsy). Biopsied patients were older, with larger tumours and a greater proportion with high-risk histology. In multivariate analysis that included all factors associated with local recurrence in univariate analysis, only high-risk histology (hazard ratio [HR] = 2.32; 95% confidence interval [CI]: 1.58–3.42, p=<0.0001), age≥2 years (HR = 2.24; 95% CI: 1.22–4.09, p = 0.01) and preoperative tumour volume (HR = 1.07 per 100 ml; 95% CI: 1.02–1.12, p = 0.01) were significant. The HR for the association of local recurrence and event-free and overall survival with biopsy was not significant (HR = 1.4; 95% CI: 0.9–2.17, p = 0.13; HR = 1.1; 95% CI: 0.85–1.42, p = 0.46 and HR = 1.13; 95% CI: 0.79–1.62, p = 0.51, respectively). These results were not materially different whether FNA or open biopsy were included in the biopsy group or not. Conclusions: This post hoc analysis provides some reassurance that needle biopsy is not an independent adverse factor for either local recurrence or survival after adjustment for all relevant risk factors. Needle biopsy should not be an automatic criterion to 'upstage' WT. Highlights: Biopsy is not associated with local relapse in multivariable analysis. Results for local relapse are similar for fine needle or cutting needle biopsy. Automatic 'upstaging' is unnecessary in needle biopsied Wilms tumour. Open biopsy may carry greater risk and should not be used routinely. Biopsy should be reserved for cases with atypical clinical or radiologic features.